3-D Numerical Simulation of Pulsatile Blood Flow Through Healthy and Stenosed Aortoiliac Bifurcation - Harris, Josephina; Ghosh, Bhavna Singh; Paul, Ajit (Communications in Mathematics and Applications, 2024)
The objective of this study is to examine the effect of pulsatile flow of blood on hemodynamic parameters in aortoiliac bifurcation with 0% and 71% occlusion in the infrarenal aorta. The three-dimensional model with 0% stenosis was generated from Magnetic Resonance Imaging data; further the 3D model with severe stenosis was constructed. Blood was considered Newtonian in nature and the two-equation \(k-ε\) turbulence model was used to simulate the flow. Maximum and minimum pressure drop was recorded at peak systole and diastolic phase, respectively across the severe stenosis. Maximum velocity is attained at peak systole, while the streamlines show a chaotic nature due to the presence of severe stenosis. The velocity profiles at the sites of interest were examined for both the models, at the throat of severe stenosis the velocity profile becomes asymmetric, owing its asymmetry to the formation of vortices and curvature of the artery. WSS variation was seen majorly at the throat of stenosis with maximum WSS at peak systole. Cardioid shaped region of high turbulent kinetic energy was identified in the post stenotic region in transverse section of model with severe stenosis. The results of this study suggest that the effects of pulsatile flow of blood on hemodynamic parameters is exacerbated due to severe stenosis in Aortoiliac Bifurcation. Using computational methods for investigating the changes in hemodynamic indices and flow patterns governed by pulsatile flow of blood will help in developing more specific and non-invasive medical interventions for Aortoiliac Occlusive Disease (AIOD).